To the problem of introduction of the special courses in professional preparation of teachers of fine art: history of author doll - L.V. Balyuk (Academy of Cognitive and Natural Sciences, 2006)
To the problem of introduction of the special courses in professional preparation of teachers of fine art: history of author doll as the mean of development of creative capabilities of students of artistically-graphic faculties. In the article, becoming author doll is examined as the considerable constituent of artistic creation of humanity. The analysts of evolutional development of author doll is interpreted as method of development of creative capabilities of students ofartisttcalfy-gruphic faculties.